Proper names for the devil in Lithuanian dialects and folklore - Jasiūnaitė, Birutė (Baltistica, 2017)
In the Lithuanian dialects and folklore, 22 different proper names for the devil have been recorded. Together with their vernacular variants found in various regions of Lithuania, the number would be close to 50. Usually they are names used in the Christian tradition, names for the devil used outside the Christian tradition occur rather seldom. The present article discusses the origin, formation and function of devil‘s names. Devil‘s names in the Christian tradition may have originated from Hebrew, Greek, Latin, or more rarely from the Germanic or Slavic languages. The devil in etnic culture is often perceived as an anthropomorphic character, theirfore, the anthroponyms that are used to refer to him reflect a conventional diversity of Christian names in Lithuanian quite well. The greatest variation (phonetic, morphological, word formation differences) is characteristic of the proper names for the prince of hell. Anthroponyms tend to turn into euphemisms for the devil because they do not have a lexical meaning. Proper names for the devil in folklore texts may perform five different functions: appellative, magic, euphemistic, pragmatic, and apotropaic.